PENGARUH TIKTOK ADS DAN BLACK CAMPAIGN TERHADAP PERILAKU PEMBELIAN KONSUMEN DI KOTA BATAM - R. Ilham Ramizan Fahris; Madison, Felix; Putra, Andiko Damar; Birra, Bimo; Ababil, Aelwen (Jurnal Sistem Informasi (JUSIN), 2025)
The use of social media platforms such as TikTok as a tool for digital marketing continues to grow along with the increasing number of users, both for building brand awareness through TikTok Ads and indirectly through black campaigns. This study aims to analyze the influence of TikTok Ads and Black Campaigns on consumer purchasing behavior in Batam City. A quantitative method was employed by distributing online questionnaires to active TikTok users using stratified disproportional random sampling. Data analysis was conducted using SPSS software, including validity and reliability tests, multiple linear regression, and classical assumption testing. The results show that both TikTok Ads and Black Campaigns have a positive and significant influence on consumer purchasing behavior, with B coefficients of 0.360 and 0.390, respectively. These findings indicate that although black campaigns are negative in nature, their exposure can trigger consumer curiosity about the highlighted product. The implications of this study suggest that business actors need to be more selective and adaptive in developing digital marketing strategies, as consumer perceptions are influenced not only by positive promotions but also by the negative narratives circulating online. Therefore, ethical and fact-based communication strategies are key to maintaining consumer trust and brand reputation in the digital era.